Seed Predation of Interseeded Cover Crops and Resulting Impacts on Ground Beetles. Issue 4 (12th April 2021) - Carabajal-Capitán, Sara; Kniss, Andrew R; Jabbour, Randa
Abstract: Interseeding cover crops into standing grains can promote both agronomic and environmental benefits within agroecosystems. Producers must decide which cover crops are the best fit for their goals, and whether diverse cover crop mixtures provide benefits that are worth the increased seed cost. Broadcast seeding is an accessible strategy to try interseeding but can lead to patchy establishment; it is unknown how much seed loss is due to seed predators. In a two-year study, six cover crop species—planted as either single species or mixtures—were interseeded into standing corn. We evaluated seed predation at the time of seeding, agronomic impact through cover crop, and weedy biomass at the end of the season, and conservation impact through activity-density of ground beetles (Coleoptera: Carabidae). Cover crop seeds were vulnerable to seed predation, primarily by vertebrate seed predators, and seed loss varied across cover crop species. Cover crop biomass did not differ according to cover crop diversity and weedy biomass was not affected by cover crop presence or species. Cover crop diversity effects on carabid activity-density were inconsistent: carabids were higher in diverse mixtures in 1 year of the study, but only predicted by vegetative cover, not by cover crop, in the second year. Interseeding cover crops into corn has potential benefits for ground beetles, although the value of mixtures must be further explored.